ULTICULTURAL-BASED EDUCATION MANAGEMENT AT THE BHINNEKA DANCE STUDIO IN DANDONG VILLAGE, SRENGAT, BLITAR, EAST JAVA - Almeyra, Dhea; Handaningrum, Warih (Solah, 2025)
This study aims to describe and analyze the application of multicultural-based educational management at Sanggar Tari Bhinneka, Dandong Village, Srengat District, Blitar Regency, East Java. The primary focus of this study is how management functions—including planning, organizing, directing, and controlling—are implemented in non-formal education activities based on the arts, as well as the adaptive strategies employed in responding to changes in the times and post-pandemic challenges. The research method used is descriptive qualitative, with data collection techniques including observation, structured interviews, and documentation. The research findings indicate that the Bhinneka Dance Studio successfully applies an inclusive, flexible, and multicultural-oriented management approach. This is reflected in the training system that considers the diversity of participants' backgrounds, a participatory organizational structure, and collaborative strategies to maintain the studio's existence through digitalization and art-based entrepreneurship. These findings reinforce the relevance of multicultural education management theory as an effective framework for managing heterogeneous community-based arts institutions. Keywords: Education management, multiculturalism, dance studio, non-formal education